Peran Pendidikan Agama Islam Dalam Pembentukan Karakter Sosial Dalam Bermasyarakat - Khurin In'Ratnasari; Yovita Dyah Permatasari; Mar’atus Sholihah (STAIFAS-Press, 2020)
Islamic religious education is very important for shaping character, especially in social society. In today's era, students tend not to care about society, therefore forming a good character is very important, especially in the social community in Islamic religious education itself, it teaches us that we are required to have good character as taught by the Prophet Muhammad; Allah SWT said, which means